Acute drug reaction and non-compliance to anti-tuberculosis medications: a case study - Mahmud, Aidalina; Mohd Shah, Ashwinni; Rajandran, Darsayini; Yusof, Khalida (Community Health Society Malaysia, 2014)
Introduction: Tuberculosis (TB) is a significant re-emerging disease in Malaysia. TB treatment involves prolonged use of antibiotics, but adverse drug reaction and non-compliance to anti- tuberculosis drugs hamper the success of treatment. Case report: A 59 year old man with underlying diabetes and hyperlipidaemia presented with a four-day history of vomiting and diarrhoea. He was diagnosed with smear negative pulmonary TB three weeks earlier and was on TB medications. Apart from reduced air entry at both lung apices, the physical examination was normal. All blood results were normal except mild derangement of the renal profile and raised monocyte count. The patient had poor knowledge, insight and attitude towards his illness. Conclusion: We report a case of acute drug reaction and non-compliance to anti-TB, and the possible associated factors. Knowledge, insight and proper attitude are vital in ensuring the patient’s treatment compliance.